2016
DOI: 10.21776/ub.jkb.2016.029.02.9
|View full text |Cite
|
Sign up to set email alerts
|

Tingginya Prevalensi MRSA pada Isolat Klinik Periode 2010- 2014 di RSUD Dr. Saiful Anwar Malang, Indonesia

Abstract: ABSTRAKMethicillin Resistant Staphylococcus aureus (MRSA) merupakan bakteri patogen terpenting penyebab infeksi terkait perawatan di rumah sakit di dunia. Penelitian ini bertujuan untuk membandingkan prevalensi dan pola resistensi antibiotik dari isolat MRSA di RSUD Dr. Saiful Anwar Malang, Jawa Timur, Indonesia selama kurun waktu [2010][2011][2012][2013][2014]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…20 A study conducted at Dr. Saiful Anwar Hospital found that predominant isolates of MRSA from pus were 49%, this results similar to this study. 21 This study carried out the polymerase chain reaction on 23 MRSA isolates. It was found that 17 isolates (73.91%) had SCCmec type III and pvl genes.…”
Section: Methodsmentioning
confidence: 99%
“…20 A study conducted at Dr. Saiful Anwar Hospital found that predominant isolates of MRSA from pus were 49%, this results similar to this study. 21 This study carried out the polymerase chain reaction on 23 MRSA isolates. It was found that 17 isolates (73.91%) had SCCmec type III and pvl genes.…”
Section: Methodsmentioning
confidence: 99%
“…Salah satu patogen resisten adalah MRSA (Methicillin-resistant Staphylococcus aureus). MRSA merupakan patogen nosokomial yang dapat menyebabkan penyakit infeksi kulit dan jaringan lunak, seperti impetigo, endokarditis, bahkan sepsis (Erikawati et al, 2016;Grema, 2015). WHO (World Health Organization) melaporkan bahwa MRSA termasuk dalam prioritas tinggi patogen resisten yang harus diatasi dengan menggunakan agen antibakteri baru (WHO, 2017).…”
Section: Pendahuluanunclassified
“…One of the causes of infectious diseases is bacteria. S. aureus is capable of causing various infections with different levels of severity in soft tissue, bone tissue, respiratory organs, and endovascular tissue (Erikawati et al, 2016). Meanwhile, E. coli bacteria commonly cause diarrhea, urinary tract infections, pneumonia, wound infections, especially in the abdomen, and meningitis (Suryati et al, 2017).…”
Section: Introductionmentioning
confidence: 99%